2022
DOI: 10.1111/eea.13156
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition site selection in the crepuscular moth, Grapholita molesta: does light matter?

Abstract: Some insects that particularly prefer sunny or shaded sites use light intensity to locate suitable oviposition sites during the day. However, it is not known whether crepuscular species can be guided by light for oviposition under dim or variable light conditions. We used the crepuscular moth Grapholita molesta (Busck) (Lepidoptera: Tortricidae), a major pest of stone and pome fruits worldwide, to investigate oviposition response to light at various intensities (1000, 100, 10, and 1 mW m −2 ). Light intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Tortricids show preference when given a choice of traps of different colours (Knight and Miliczky, 2003;Myers et al, 2009;Zhao et al, 2013;Rayegan et al, 2016). In addition, mated females of G. molesta show colour and light intensity oviposition preferences under laboratory conditions (Yang et al, 2020(Yang et al, , 2022. Tortricid moths are an economically important group for which the alternative to insecticide control is mostly based on odour-baited traps and mating disruption with sex pheromones (Knight et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tortricids show preference when given a choice of traps of different colours (Knight and Miliczky, 2003;Myers et al, 2009;Zhao et al, 2013;Rayegan et al, 2016). In addition, mated females of G. molesta show colour and light intensity oviposition preferences under laboratory conditions (Yang et al, 2020(Yang et al, , 2022. Tortricid moths are an economically important group for which the alternative to insecticide control is mostly based on odour-baited traps and mating disruption with sex pheromones (Knight et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, they use vision to fly and to navigate in odour plumes (Navarro-Roldán et al, 2019), and probably to recognize and land on the host plants. Vision could also be involved in mating and oviposition behaviour (Yang et al, 2020(Yang et al, , 2022. Colour has some effect on the capture of males in pheromone traps (Knight and Miliczky, 2003;Knight and Fisher, 2006;Zhao et al, 2013;Padilha et al, 2018;Rayegan et al, 2016), and UV light appears to influence male but not female captures in semiochemical traps (Adasme, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has however been observed that adult Grapholita molesta are attracted to light, preferring violet and green light ( Sun et al, 2014 ). Our recent works show that G. molesta can visually discriminate between plants in microhabitats to guide oviposition even in dim light, exhibiting a preference for higher brightness/intensity ( Yang et al, 2020 ; 2022 ). Electroretinogram (ERG) spectral sensitivity measurements additionally reveal that three photoreceptor classes are present in compound eyes of G. molesta , with sensitivities peaking at UV (355 nm), blue (440 nm) and green (525 nm) wavelengths ( Martín-Gabarrella et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%